The Rodgers and Hammerstein story. - Green, Stanley (W. H. Allen, 1963)
A dual biography of the men whose musical partnership gave America such productions as Oklahoma, Carousel, South Pacific, The King and I, and The Sound of Music. Includes a list of all the songs they wrote.